Zinc‐containing yeast extract promotes nonrapid eye movement sleep in mice. Issue 10 (7th July 2015) - Cherasse, Yoan; Saito, Hitomi; Nagata, Nanae; Aritake, Kosuke; Lazarus, Michael; Urade, Yoshihiro
<x xml:space="preserve">Abstract</x> Zinc is an essential trace element for humans and animals, being located, among other places, in the synaptic vesicles of cortical glutamatergic neurons and hippocampal mossy fibers in the brain. Extracellular zinc has the potential to interact with and modulate many different synaptic targets, including glutamate and GABA receptors. Because of the central role of these neurotransmitters in brain activity, we examined in this study the sleep‐promoting activity of zinc by monitoring locomotor activity and electroencephalogram after its administration to mice. Zinc‐containing yeast extract (40 and 80 mg/kg) dose dependently increased the total amount of nonrapid eye movement sleep and decreased the locomotor activity. However, this preparation did not change the amount of rapid eye movement sleep or show any adverse effects such as rebound of insomnia during a period of 24 h following the induction of sleep; whereas the extracts containing other divalent cations (manganese, iron, and copper) did not decrease the locomotor activity. This is the first evidence that zinc can induce sleep. Our data open the way to new types of food supplements designed to improve sleep.